Nós precisamos de mais espécies de tetrápodas? - Jardim, Lucas Lacerda Caldas Zanini (2014)
We have been describing species for a long time and we have been asking about how many of them are left on the Earth. Species are evolutionary lineages and the answer to that question maybe is not in richness estimates, but in how much of the evolutionary tree was already described. Here, we studied how richness and phylogenetic diversity have been accumulated in Tetrapods and how those metrics differ from each other. We also tested if there were biases for particular clades in species describing process, it would mean non-random description along the phylogeny. We found Amphibia and Squamata have ascendant curves for both metrics, Mammals are beginning its stabilization and Birds are stabilizing for about 60 years. Nonetheless, phylogenetic diversity trends to stabilize firstly than richness, due to the convex relationship between them. We also founde that description has been at random about clades. Thus, more efforts are necessary to improve our phylogenetic resolution of Amphibia, Squamata and Mammals. Once we have an ample sample size in Birds and a random sample along phylogeny, we need to resolve Darwinian and Wallacean shortfalls, taking into consideration the phylogenetic relationship among species, the evolutionary model of their traits and where those species occur. Understanding species as lineages permits us to stabilize early the number of species and to infer which species could have been extinct before description, such as what would be their impacts in conservation, community ecology and ecosystem function.